The Study of Relation Between Normal and Higher than Standard Concentration of Sodium of Drinking Water in Ascites Syndrome Declaration in Broiler Chickens - Kiani, Rezvan; Feizi, Adel (International Journal of Poultry Science, 2007)
Eight drinking water trials were conducted to study the tolerance of young chickens to various concentrations of sodium of drinking water. Chickens tolerated 40 ppm of sodium of drinking water from hatch to seven weeks of age without harmful effects as judged from the data on mortality rate, feed intake, body weight, ascite fluid presence, heart injuries and plasma sodium and protein amounts. High mortalities with ascites and heart injuries occurred in chickens that drank drinking water which its sodium concentration was 350 ppm. Mortalities had a direct relation with increase in levels of sodium in drinking water.